2006
DOI: 10.1103/physrevb.73.155325
|View full text |Cite
|
Sign up to set email alerts
|

Quantum rings as electron spin beam splitters

Abstract: Quantum interference and spin-orbit interaction in a one-dimensional mesoscopic semiconductor ring with one input and two output leads can act as a spin beam splitter. Different polarization can be achieved in the two output channels from an originally totally unpolarized incoming spin state, very much like in a Stern-Gerlach apparatus. We determine the relevant parameters such that the device has unit efficiency.Comment: 4 pages, 3 figures; minor change

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
121
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(126 citation statements)
references
References 34 publications
(48 reference statements)
5
121
0
Order By: Relevance
“…This symmetric case was explored in a ring interferometer in Ref. 23. However, the conditions (26) can be fulfilled also when the two arms of the interferometer are not precisely identical, since the condition y b = y c does not require the arms bd and cd to be identical.…”
Section: Three-terminal Diamond Interferometermentioning
confidence: 99%
See 1 more Smart Citation
“…This symmetric case was explored in a ring interferometer in Ref. 23. However, the conditions (26) can be fulfilled also when the two arms of the interferometer are not precisely identical, since the condition y b = y c does not require the arms bd and cd to be identical.…”
Section: Three-terminal Diamond Interferometermentioning
confidence: 99%
“…[13][14][15][16][17] Alternatively, one may increase the number of terminals connected to the device and thus generate a finite spin polarization without exploiting ferromagnetic electrodes and without applying magnetic fields. Allelectrical single-loop spin filters based on three-terminal devices have been studied before; [20][21][22][23][24] in particular, Földi et al 23 demonstrated that a symmetric-ring interferometer attached to one source and two drain terminals can act as a spin beam-splitter, which polarizes the electrons in the output leads along tunable directions. In the first part of this paper we extend this result to a more realistic setup.…”
Section: Introductionmentioning
confidence: 99%
“…Some papers also suggested to connect the loop to three leads, as in a Stern-Gerlach experiment. 52,53 However, the calculated criteria for filtering in these papers were usually energy-dependent, and there was no systematic discussion of these criteria and of the polarization of the transmitted spins. An alternative geometry replaces the circular loop by a diamond-shaped square, with a SOI on its four edges (which determine ω) and with a penetrating AB flux, see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier works have proposed junction S matrix for solving the scattering problem of a ring [10][11][12][13][14][15][16][17]23,24 where the following conditions are satisfied at the junction: (a) conservation of current, (b) continuity of wave function and (c) unitarity of S matrix. However, earlier models do not account for channel mixing and also do not allow us to include evanescent modes.…”
Section: S -Matrix For the Junctionmentioning
confidence: 99%
“…These devices can be exploited if we achieve the technology that can reduce or control the phase fluctuations to a small fraction of 2π 9 . A lot of work has been done in one dimensional quantum rings [9][10][11][12][13][14][15][16][17][18] . However, the experimental rings are always in two dimension or in three dimension.…”
Section: Introductionmentioning
confidence: 99%